Antibacterial and antioxidant potentials of methanol extract and secondary metabolites from Wualae rhizome (Etlingera elatior) - Wahyuni; Sri Hutami Lety Grashella; Wa Ode Ida Fitriah; Muhammad Hajrul Malaka; Adryan Fristiohady; Imran; Sahidin (Institut Teknologi Bandung, 2019)
The rhizome of Etlingera elatior or Wualae (Tolakinese) has many advantages on traditional remedies and cooking in Sulawesi Tenggara. To support those advantages, two secondary metabolites derived from steroid and phenylpropanoic acid classes, stigmast-4-en-6β-ol-3-one (1) and p-coumaric acid (2), respectively, have been firstly isolated and identified from the E. elatior rhizome. Isolation of these two compounds was performed using several chromatography techniques, including thin layer chromatography (TLC), vacuum liquid chromatography (VLC) and radial chromatography (RC). Identification of isolates was carried out using 1 H and 13C NMR spectroscopy and comparing the spectroscopy data with the library. The potency of antibacterial of the methanol extract of Wualae rhizome and the isolates were evaluated against Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis FNCC 0060, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 35218, Salmonella enterica ATCC 14028, and Streptococcus mutans ATCC 25175 using agar diffusion method. Antioxidant activity was evaluated against DPPH radicals (2,2-diphenyl-1-picrylhydrazyl). The results show that the antibacterial potential of Wualae methanol extract is better than compound 1 and 2. Furthermore, the antioxidant properties of Compound 2 (IC50 159.47 μg/mL) was stronger than the antioxidant properties of Compound 1 (IC50 219.95 μg/mL) and the methanol extract (IC50 586.38 μg/mL).